On the Instrumental Measurement of Line Shape under Water - Carruthers, J. N.; Woods, A. J.; Lee, A. J. (The International Hydrographic Review, 2018)
After a short review of the problems arising from wire-angle, and a consideration of some views expressed and results obtained by earlier writers, a description is given of two devices designed to measure the shape of terminally-weighted wires let down into the sea with water-bottles attached. Both devices can be used intermediately between water bottles and, whilst customarily operated by messengers, they can function via the solution of restraining tablets. One of them contains a compass which serves to reveal the directions of those curvatures in a loaded suspension wire which can be produced when deep currents cause a pronounced leading-away of a wire whose departure angle is kept negligible by manoeuvring the ship. Particular usefulness is seen for the devices when bottle lowerings have to be made well below the depth limit of unprotected reversing thermometers. This latter is usually about 5,500 metres but very exceptionally 7,000 metres. Finally a description is given of a very simple device which records the slant of a rope buoyed from an anchor. The purpose in this case is to learn the heights above bottom at which an affixed current-meter has worked.